Multi-view Video Coding for 3DTV - Abd Manap, Nurulfajar (2010)
With the advent in display technology, the 3DTV will provide a new viewing experience without the need of wearing special glasses to watch the 3D scenes. One of the key elements in 3DTV is the multi-view video coding; obtained from a set of synchronized cameras, capture the same scene from different viewpoints. The video streams are synchronized and subsequently used to exploit the redundancy contained among video sources. A multi-view video consists of components for data acquisition, compression, transmission and display. This paper outlines the design and implementation of a multi-view video system for transmission over a wireless channel. Synchronized video sequences acquired from four separate cameras and coded with H.264/AVC.